Lo stereotipo del Sud fra Otto e Novecento. Il caso della Sardegna - Urban, Maria Bonaria (Incontri. Rivista europea di studi italiani, 2011)
The Southern Stereotype in the 19th and 20th Centuries. The Case of Sardinia Following Italian unification, the North-South dichotomy which had for centuries been part of European tradition was reformulated in Italian culture, resulting in the definition of a homogeneous concept of the South and with it what is probably the most significant and persistent stereotype in the national collective imagination. This perspective stands as a constant in every text on Sardinia, since the national debate on the Southern Question placed the island firmly among the country’s other Southern regions. In the early 20th century the traditional stock of images and stereotypes characterising literary discourse became an essential reservoir of characters, situations and places for film-makers. Following the method of imagology, this paper focuses on the strategies used in representing the stereotype of the South in the cinema, specifically in the film Cainà. L’isola e il continente (Righelli 1922). The working hypothesis is that films confirmed the centrality of the North-South dichotomy as the creative engine in the Italian cinematic imagination and the identification of Sardinian society with the South perceived as a model of archaic and primitive civilisation. Depicting Sardinia in accordance with an interpretative scheme considered absolute and unchanging, the new art form followed a route already laid down in literature. In addition, in a cultural phase dominated by the need to develop and disseminate a national consciousness, it contributed to the production of images and symbols standing in open contradiction to the ideal of a united Italy, revealing the contradictions that the Risorgimento had created rather than resolve.